Clinical application of the new cardiovascular risk prediction algorithms SCORE2 and SCORE2-OP in patients with dyslipidemia. (11th May 2022) - Barkas, F; Sakkou, SF; Styla, C; Anastasiou, G; Koutsogianni, AD; Liamis, G; Liberopoulos, E
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: European Society of Cardiology (ESC) has recently launched the SCORE2 and SCORE2-OP cardiovascular risk prediction algorithms. Purpose: Cardiovascular risk assessment of patients with dyslipidemia according to SCORE2 and SCORE2-OP in comparison with the HELLENIC SCORE. Methods: A retrospective observational study involving 1334 dyslipidemic patients followed-up for ≥3 years at our outpatient lipid clinic in our university general hospital. After excluding patients with established cardiovascular disease, diabetes mellitus, familial hypercholesterolemia, chronic renal disease, and those receiving hypolipidemic treatment, patients were categorized according to HELLENIC SCORE and SCORE2 / SCORE2-OP into the following cardiovascular risk groups: low-moderate, high and very high. Results: A total of 532 patients were included in the present analysis (40% male, 17% smokers, mean age 55 [48-62] years, 8.6%> 70 years). Subjects' mean cholesterol levels were 257 (228-291) mg/dL, triglycerides 136 (99-196) mg/dL, high-density lipoprotein cholesterol 52 (45-62) mg/dL, and low-density lipoprotein cholesterol 173 (149-200) mg/dL. According to SCORE calculation, 428 patients (80%) were classified into low-moderate, 87 (17%) high and 17 (3%) very high cardiovascular risk group. According to SCORE2 and SCORE2-OP algorithms, the proportion of those considered as high (n=230, 43%) and very high cardiovascular risk (n=89, 17%) increased (Figure). Conclusions: The proportion of patients classified into high and very cardiovascular risk groups is anticipated to increase by implementing the new SCORE2 and SCORE2-OP.